Persepsi guru Matematik terhadap penggunaan bahan media dalam pengajaran Matematik - Ng, Sok Hooi (2008)
The purpose of the study is to identify the relationship between the variables of teacher's perception towards the usage of media materials in teaching mathematics in secondary schools in Perlis. This study also identifies the differences in teachers' perception based on gender. A total of 181 mathematics teacher is involved as the respondents. The data is collected through questionnaires and analyzed using SPSS version 12. The results of the study reveal that there is a positive significant relationship between the skill variables and facilities provided, skill and effectiveness of usage media materials, facilities provided and effectiveness of usage media materials and facilities provided and problems faced. The results also show a negative significant relationship between the skill variables and problems faced and effectiveness of usage media materials and problems faced. The results of the study also indicate that there is a significant difference in perception between male and female teachers towards the usage of media material in teaching mathematics. The male teachers' perception is higher than female teachers. Through the findings, it is clear that the usage of media materials is important in the teaching of mathematics. Nevertheless, a good planning need to be carried out prior before using the media materials and these materials must also be used appropriately and relevant to the subject matter. In this way, the teaching of mathematics in the secondary schools will be more effective and efficient.